The association of reported respiratory symptoms among children in Malaysia with particulate matter exposure in municipal solid waste landfills - Jamaluddin, Dora Esphylin; Syed Ismail, Sharifah Norkhadijah; Praveena, Sarva Mangala; Hashim, Zailina; Zainal Abidin, Emilia (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Background: Prolonged exposure of heavy metals in the respirable particulate matter (PM10) from municipal solid waste (MSW) landfills may affect children health. Objective: To investigate the association of reported respiratory symptom with heavy metals in PM10, with heavy metals in fingernails among children residing close to MSW landfills. Methods: Two groups of children age 7 to 12 years old were involved in this cross-sectional study. Those residing within 3 km radius from a landfill were the exposed group and those residing more than 3 km radius as the unexposed group. Questionnaires adapted from American Thoracic Society were applied in the survey. Fingernails were used as biomarker. Ten heavy metals elements in PM and fingernail samples were analysed using inductively coupled plasma mass spectrometry (ICP-MS). Results: The cadmium, chromium, copper, manganese, nickel and lead concentrations in PM around the MSW landfills and residential areas exceeded the Canada and USEPA standard permissible limit. Heavy metals in fingernails (p<0.001) of exposed group were significantly higher than the unexposed group. Children with no pets have less reported respiratory symptoms. Elevated level of heavy metals in PM and fingernails were associated with high risk of reported respiratory symptoms. Conclusion: Heavy metals in PM10 and fingernails were associated with potential risk factor of respiratory health in children.